Hubungan Pengetahuan dan Sikap Tentang Personal Hygiene pada Santriwati dengan Kejadian Pediculosis Capitis di Pondok Pesantren Al-Manshur Popongan - Sari Rohmaniah; Eska Dwi Prajayanti (Yayasan Literasi Sains Indonesia, 2022)
Pediculosis Capitis is an infection of the skin or hair of the head caused by the infestation of Pediculus Humanus Var. Capitis. Factors causing Pediculosis Capitis is an environment with many residents such as in a boarding school, the lack of knowledge and attitudes of personal hygiene such as rarely shampooing and individual characteristics (types of hair and hair length). This study aims to determine the relationship between knowledge and attitudes about personal hygiene in students with the incidence of pediculosis capitis in the cottage Pesantren Al-Mansur Popongan. This research method uses the cross-sectional. The sample of this research is the female students of Al-Manshur Popongan Islamic Boarding School. technique This research uses purposive sampling data analysis chi-square test. Data retrieval through filling out questionnaires and direct examination of samples. most of the female student had sufficient knowledge of personal hygiene category, 43 female student (64.2%), personal hygiene attitude positive category 42 female student (62.7%) and for the incidence of pediculosis capitis yes category 50 female student (74.6%). The results of the chi square test with P-value 0.017 < 0.05 and P-value 0.001 < 0.05. there is a significant relationship between knowledge and personal hygiene in female students with the incidence of pediculosis capitis at the Al-Manshur Popongan Islamic Boarding School.